The sense of brown - Muñoz, José Esteban 1967-2013 (Perverse modernities, 2020)
The Sense of Brown, which he was completing at the time of his death, is José Esteban Muñoz's treatise on brownness and being as well as his most direct address to queer Latinx studies. Muñoz examines the work of playwrights Ricardo Bracho and Nilo Cruz, artists Nao Bustamante, Isaac Julien, and Tania Bruguera, and singer José Feliciano, among others, arguing for a sense of brownness that is not fixed within the racial and national contours of Latinidad. This sense of brown is not about the individualized brown subject; rather, it demonstrates that for brown peoples, being exists within what Muñoz calls the brown commons-a lifeworld, queer ecology, and a form of collectivity. In analyzing minoritarian affect, ethnicity as a structure of feeling, and brown feelings as they emerge in, through, and beside art and performance, Muñoz illustrates how the sense of brown serves as the basis for other ways of knowing and being in the world